Pengaruh Likuiditas, Kualitas Aset, Sensitivitas, Efisiensi Terhadap Profitabilitas Pada Bank Umum Devisa KBMI IV - Meraldi Galang Putra Poernomo; Sri Haryati (Cakrawala Repositori IMWI, 2023)
The purpose of this research is to analyze the effect of liquidity, asset quality, sensitivity and efficiency on profitability as measured using ROA. Liquidity is measured using the Loan to Deposits Ratio (LDR) and investing policy ratio (IPR). Asset quality is measured by the ratio of Non Performing Loans (NPL) and Non-Performing Earning Assets (APB). Sensitivity is measured using the interest risk ratio (IRR) and net open position (PDN). Efficiency is measured by Operational Cost Operating Income (BOPO) and Fee Based Income Ratio (FBIR). The sample used in this study is the Foreign Exchange Commercial Bank KBMI IV with the period from the first quarter of 2018 to the second quarter of 2022. The analysis technique used is multiple linear regression analysis using SPSS 26. The conclusions in this study are LDR, IPR, NPL, APB, IRR, PDN, BOPO and FBIR simultaneously have a significant effect on ROA. The ratios of LDR, IPR, NPL, BOPO, FBIR partially have a significant negative effect on ROA. The ratio of APB, PDN partially has no significant negative effect on ROA. The IRR ratio partially has a significant positive effect.